Insight into the role of polyacrylamide polymer powder on the cracking in plastic period of cement mortar. (10th November 2020) - Li, Haoxin; Ni, Dayou; Li, Lin; Dong, Biqin; Chen, Qing; Gu, Linan
Highlights: It improves the resistance to the cracking in the plastic period. It decreases water evaporation loss and bleeding percentage. Intermolecular hydrogen bonds form in the solution with cement. It especially promotes the cement hydration at initial reaction. Abstract: It is still uncertain whether polyacrylamide polymer powder can restrain the cracking of cement mortar in the plastic period and the mechanisms, which are responsible for this role, still need to be systematically clarified. Thus the different contents of the polyacrylamide polymer powder were mixed and various pastes with polyacrylamide were prepared. The cracking behaviors and water evaporation losses of mortars were evaluated. The bleeding percentages, chemical shrinkages, ions concentrations, ultraviolet visible spectra and the characteristics of hydration heat liberations of cement pastes with polyacrylamide polymer powder were investigated to carry out the insight into the role of polyacrylamide polymer powder on the cracking of cement paste in the plastic period. The experimental results indicate that the polyacrylamide polymer powder improves the mortar resistance to the cracking in the plastic period. It decreases the water evaporation loss and bleeding percentage. But it enhances the chemical shrinkage and the increased chemical shrinkage is mainly attributed to the role of polyacrylamide polymer powder on the promotion of cement hydration in the tested ages, especially in the initial fast reaction and the first deceleration periods. The existence of the intermolecular hydrogen bonds is the main reason for lowering the water evaporation loss and bleeding percentages. Acting forces from the intermolecular hydrogen bonds may be additional contributor to the improved resistance to the cracking of cement mortar in the plastic period. The results from this work will provide a reference for the alleviation of the plastic cracking of cement based paste.